Сlinical results of transepithelial corneal collagen crosslinking in patients with keratoconus - M. M. Bikbov; V. K. Surkova; G. M. Bikbova; N. B. Zainullina (Oftalʹmologiâ)
Purpose: To evaluate the clinical results of transepithelial corneal collagen crosslinking (CXL) compared with the standard CXL in patients with keratoconus.Patients and methods. There were 94 patients (119 eyes) with I‑III stage keratoconus (according to the Amsler classification) under observation since 2011 to 2013. The first group included 43 patients(56 eyes) among them 11 patients (11 eyes) with an initially thin cornea (380‑430 microns) underwent transepithelial CXL. 51 patients (63 eyes) in the second group — the standard CXL. Saturation of the cornea with a photosensitizer during transepithelial CXL was performed via electrophoresis using the «Potok-1» device, in the amperage of 1 mA for 10 minutes. CXL was performed with the use of «UFalink» device and «Dextralink» photosensitizer.Results. Pseudo haze of corneal stroma was diagnosed on biomicroscopy after both methods of CXL. In the 1st group in 38 % of cases (30 eyes) it disappeared in 2‑4 weeks after the CXL, in the 2nd group in 100 % of cases (63 eyes) it resolved in 3‑4 months, on average, after the treatment. According to optical coherence tomography (OCT) in two weeks after transepithelial CXL there was a demarcation line in 27 eyes (48.2 %) after 1 month — in 15 (26.7 %), at a later stage — has not been determined. After a standard CXL demarcation line was determined during the first two weeks in all patients (100 %) and persisted until 12 months in 2 eyes (3.5 %). Indicator of cornea’s refractive power in 2 years after transepithelial CXL decreased by 1.5 D (p> 0.05) compared to baseline values after standard CXL decreased by 1.8 D (p>0.05). Uncorrected visual acuity after transepithelial CXL increased from 0,31±0,01 to 0,45± 0,05 (p<0.05) in 2 years, after the standard CXL — from 0,27±0,03 to 0.3±0,05 (r≥0,05). Corrected visual acuity (CVA) in both groups tended to increase over the two-year followup. The obtained comparable results showed that the use of transepithelial and standard methods of CXL in patients with keratoconus prevents disease progression in 73.2 % and 77.7 % respectively what confirms the possibility of its equal usage in clinical practice.Conclusion. Transepithelial CXL with photosensitizer saturation by electrophoresis does not require de-epithelization, it’s well-tolerated and does not cause pain. This technique is equa the standard CXL procedure. It improves optometric data and stabilizes the disease process.